Concepts in the book of poems The Midday by Antonina Belova - Брызгалова, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
This article addresses the concepts in the book of poems The Midday by Antonina Belova, which was published in 2009. The author highlights the core concepts ("beauty", "faith", "love", "memory") and shows their internal connections. Semantic borders of the concepts are often blurred; their fields vary, forming a semantic and emotional unity, which includes the originality of poems by Antonina Belova.